Effective and Necessary Professional Development for Science Teachers as States Adopt NGSS - Anne M Krebs (Adult Education Research Conference, 2017)
This roundtable will explore the efficacy of professional development opportunities designed to support science teachers during the transition to the Next Generation Science Standards (NGSS).
Keywords: NGSS; professional development; continuing professional education; science